2019
DOI: 10.1039/c9sm01565e
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization in soft nanoconfinement of lamellar and reverse hexagonal mesophases

Abstract: The polymerization rate decreases in the nanoconfined structure compared to the bulk state due to the segregation effect, which increases the local monomer concentration and enhances the termination reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…When these materials are extruded through a nozzle or die, the nano entities may become aligned in the flow direction, which produces a highly anisotropic macrostructure resulting in improved structure related properties. Such properties are of high interest in applications such as scaffolds for catalysis and separation, [ 17 ] templating, [ 18 ] encapsulation of molecules as drug delivery agents and nanocarriers, [ 19,20 ] or as media to obtain structural data of molecules. [ 21,22 ]…”
Section: Introductionmentioning
confidence: 99%
“…When these materials are extruded through a nozzle or die, the nano entities may become aligned in the flow direction, which produces a highly anisotropic macrostructure resulting in improved structure related properties. Such properties are of high interest in applications such as scaffolds for catalysis and separation, [ 17 ] templating, [ 18 ] encapsulation of molecules as drug delivery agents and nanocarriers, [ 19,20 ] or as media to obtain structural data of molecules. [ 21,22 ]…”
Section: Introductionmentioning
confidence: 99%
“…The polymerization of the mesophases was performed in an oven at 70°C for 24 h. The monomer conversion in polyLLCs was approx. 90% 15 . As control samples, homogeneous mixtures of PEO/IL were prepared with the same ratio of PEO/IL as in the mesophase samples.…”
Section: Methodsmentioning
confidence: 99%
“…Several works have been reported on the morphology, ionic conductivity, glass transition temperature, and tensile strength of binary BCP/IL mixtures as function of the IL content 12,13 . In our previous work, we showed that polymerized LLCs (polyLLCs) of surfactant/water/oil and surfactant/IL/oil enable the formation of nanostructured polymers that exhibit enhanced mechanical strength while the original lamellar or hexagonal structure is retained after polymerization 14–16 . It has been suggested that by tuning the morphology and domain sizes of the self‐assembled structures, these materials could bypass the usual trade‐offs between mechanical strength and conductivity 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Porous polymers have many applications such as gas separation materials, , encapsulation agents for drug release, , membranes, catalyst supports, , sensors, cell scaffolds, and electrode materials for energy storage, to name a few. The typical methods for making interconnected porous polymers include high internal phase emulsion (HIPE) templating, block copolymer self-assembly, , direct templating, and microfluidics . These methods can be cost-intensive when dealing with micrometer-sized void structures.…”
Section: Introductionmentioning
confidence: 99%
“…The major drawback to this process is the requirement of a template that is ultimately destroyed, limiting the scalability of the material. Self-assembly methods use block copolymer systems to produce ordered structures such as lyotropic liquid-crystalline phases, which can then be polymerized into a porous polymer . However, they are usually used to make mesoporous polymers with nanometer size pores.…”
Section: Introductionmentioning
confidence: 99%